Anesthetic Considerations for a Patient With Hereditary Hemorrhagic Telangiectasia (Osler–Weber–Rendu Syndrome) Undergoing a Five-Box Thoracoscopic Maze Procedure for Atrial Fibrillation. (8th October 2014) - Robinson, Dominic; Rogers, Barbara; Kapoor, Ritu; Swan, Joseph; Speas, Gaylynn; Gutmann, Rebecca
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant genetic disorder involving the abnormal communication of vascular structures. HHT typically presents with recurrent epistaxis and telangiectasis of the nasal and buccal mucosa, tongue, and lips. More serious manifestations of this disease include cerebral, pulmonary, gastrointestinal, and hepatic arteriovenous malformations. This case report details a 55-year-old male with HHT undergoing a five-box maze procedure for curative treatment of atrial fibrillation. Particular anesthetic considerations are described to reduce morbidity and mortality in this patient population.